Understanding Newton's Third Law: A Study of Prospective Physics Teachers' Knowledge Structure - Pertiwi, Wulan Anna; Faizah, Revnika; Kusumawati, Astrini Dewi; Nadiyah, Nadiyah; Budi, Agus Setyo; Sukariasih, Luh (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2024)
This research aims to explore the ability to understand concepts and the characteristics of the knowledge structure of prospective physics teachers regarding Newton's Third Law. This research was conducted on 26 Physics Education students in their first year who had received material on Newton's Laws. The instrument used is the Force Concept Inventory (FCI) test instrument. Using four multiple-choice questions accompanied by reasons, the quantitative data source comes from students' choice of answers. In contrast, the qualitative data source comes from students' reasons for choosing answers, which are used to see the characteristics of knowledge structures. The data analysis technique used is descriptive statistics to present a picture of the ability to understand concepts and the level of character of the knowledge structure of prospective teachers. The results show that the concept understanding ability of prospective physics teachers has an average of 67.31 and is classified as sufficient. The knowledge structure characteristics of prospective physics teachers at the expert level is 62.50%, the beginner level is 14.42%, and the intermediate level is 24.04%. These results show that the ability to understand the concept of Newton's Third Law and the characteristics of knowledge structures have a coherent influence. Prospective teachers with the characteristics of an expert knowledge structure can solve physics problems using correct physics principles. These findings require further research to explore the factors influencing understanding concepts and characteristics of prospective teachers' knowledge structures and more effective teaching strategies.